Impact of moderate heat stress on the biochemical and physiological responses of the invasive waterweed Elodea canadensis (Michx. 1803) - Savicka, Marina; Petjukevičs, Aleksandrs; Batjuka, Anna; Škute, Nataļja (Archives of Biological Sciences, 2018)
Paper description: The influence of climate change on biochemical and physiological changes in freshwater macrophytes has been widely studied. Most studies have focused on the responses to stressors such as hypoxia, salinity and heavy metals. Less attention has been paid to heat-induced oxidative stress and the activity of the antioxidant system, despite the fact that elevated water temperature can severely affect them. This study provides new findings on the changes in oxidative processes, lipid peroxidation, membrane stability and antioxidant defence in aquatic macrophytes under high temperature treatment. The presented data expand on existing knowledge. Abstract: Global warming can negatively affect freshwater macrophytes. However, the degree to which freshwater plants can survive after long-term or short-term warming and the underlying molecular mechanisms are not fully understood. The aim of our study was to analyze the responses of an invasive plant to moderate heat stress (HS). Biochemical and physiological stress responses to experimental warming (30±1.0°C/25±1.0°C, day/night) were assessed in the invasive waterweed Elodea canadensis. The effect of the moderate HS on the macrophyte was evaluated through changes in the total protein content, catalase activity, lipid peroxidation, cellular membrane permeability by electrolyte leakage and the concentrations of carotenoids and photosynthetic pigments. Catalase activity and carotenoid concentrations increased significantly (p<0.01) in comparison to the control. A significant increase (p<0.05) in malondialdehyde concentration was observed. However, at the same time there was a persistent low level of electrolyte leakage in heat-treated plants as compared to the control. The results demonstrated that moderate HS improved membrane stability and increased the concentration of photosynthetic pigments and antioxidant activity in E. canadensis shoots. Moderate alterations in temperature may favorably affect the physiology and growth of the invasive macrophyte E. canadensis. It is reasonable to expect that warming could lead to a gradual change in E. canadensis distribution and to changes in composition of freshwater ecosystems. https://doi.org/10.2298/ABS180119016S Received: January 19, 2018; Revised: April 10, 2018; Accepted: April 10, 2018; Published online: April 18, 2018 How to cite this article: Savicka M, Petjukevičs A, Batjuka A, Škute N. Impact of moderate heat stress on the biochemical and physiological responses of the invasive waterweed Elodea canadensis (Michx. 1803). Arch Biol Sci. 2018;70(3):…